Internationalization and Firm Governance: The Roles of CEO Compensation, Top Team Composition, and Board Structure - Sanders, Wm. Gerard; Carpenter, Mason A. (Academy of Management Journal, 1998)
Using the complementary lenses of information-processing and agency theories, this study tests the proposition that the complexity resulting from a firm's degree of internationalization will be accommodated by its governance structure. Results from a sample of large U.S. firms support this perspective, suggesting that firms manage and cope with the information-processing demands and agency issues arising from internationalization through higher, longer-term CEO pay, larger top management teams, and the separation of chairperson and CEO positions.